Endocannabinoids and acute pain after total knee arthroplasty. Issue 2 (February 2015) - Azim, Syed; Nicholson, James; Rebecchi, Mario J.; Galbavy, William; Feng, Tian; Reinsel, Ruth; Volkow, Nora D.; Benveniste, Helene; Kaczocha, Martin
Abstract : Abstract: Osteoarthritis (OA) of the knee is a progressive disease that is associated with inflammation of the joints and lower extremity pain. Total knee arthroplasty (TKA) is a surgical procedure that aims to reduce pain and restore motor function in patients suffering from OA. The immediate postoperative period can be intensely painful leading to extended recovery times including persistent pain. The endocannabinoid system regulates nociception, and the activation of cannabinoid receptors produces antinociceptive effects in preclinical models of OA. To date, the influence of the endocannabinoid tone on pain and disability in OA patients and on acute postoperative pain in humans has not been explored. In this study, we provide the first comprehensive profile of endocannabinoids in serum, cerebrospinal fluid, and synovial fluid of patients with painful end-stage OA undergoing TKA and examine correlations between endocannabinoid levels, interleukin 6, functional disability, acute postoperative pain, and postoperative opioid use. Our results reveal that central (cerebrospinal fluid) and peripheral (synovial fluid) levels of the endocannabinoid 2-arachidonoyl glycerol were significantly elevated in patients who developed higher postoperative pain after TKA. In addition, synovial fluid 2-arachidonoyl glycerol levels were positively correlated with postoperative opioid use. Similarly, synovial fluid levels of the anti-inflammatory lipid palmitoylethanolamide correlated with functional disability in OA. Taken together, our results are the first to reveal associations between central and peripheral endocannabinoid levels and postoperative pain. This suggests that endocannabinoid metabolism may serve as a target for the development of novel analgesics both for systemic or local delivery into the joint. Abstract : Elevated levels of the endocannabinoid 2-arachidonoyl glycerol are associated with higher postoperative pain and opioid usage in patients undergoing total knee arthroplasty.